Association of cytomegalovirus and high-risk human papillomavirus with breast cancer progression: HPV and CMV in breast cancer - Majeed, Hala Mohammed; Kadhum, Sahar Jabbar; Majeed, Haider Mohammed (Cellular and Molecular Biology, 2025)
In Iraq, breast cancer is the most prevalent malignancy among women, prompting increased research in the last decade. This retrospective study aimed to determine the role of human papillomavirus (HPV) and cytomegalovirus (CMV) in breast tumors. The study included 140 formalin-fixed, paraffin-embedded breast tissue samples from 100 patients with breast tumors and 20 normal breast tissue samples as controls. Patients ranged in age from 16 to 72 years. In situ hybridization was performed on samples collected from hospitals and private laboratories in Kirkuk and Tikrit between January 15 and December 15, 2022. CMV was detected in 25% (25/100) of breast cancer tissues, while HPV was found in 45% (45/100), compared to the control group, which tested negative for both viruses. Among HPV-positive cases, HPV genotype 31 was the most prevalent (58.33%), followed by HPV16 and HPV18 (20.8% each). These findings suggest that HPV, particularly genotype 31, and CMV may play a role in breast cancer development in the Iraqi population.